Cell biology and biotechnology in space - Cogoli, A. (Augusto) (Advances in space biology and medicine, 2002)
The advent of the International Space Station ISS and the exploration by humans of planets of the Solar system like the Moon and Mars is triggering worldwide interest. Space biology, a discipline familiar so far only to a restricted community, is gaining momentum. Space biologists are dealing with the behavior of terrestrial life in the extraterrestrial environment, in particular in 0 g. Several surprising and interesting phenomena have been discovered in 20 years of investigations in space laboratories. This began with so called "fishing" experiments, i.e. investigations trying to find out, without solid hypotheses, whether a biological system is altering its behavior when exposed to zero gravity. Today's space biology is a scientific discipline based on systematic studies carried out by renowned scientists. Some of the leaders in the field describe their work, ideas and findings. This book will introduce the reader to this still young field of research which will certainly provide unexpected and significant surprises in the future.